Congenital anomalies among live births in a polluted area. A ten-year retrospective study - Gianicolo Emilio Antonio Luca; Bruni Antonella; Rosati Enrico; Sabina Saverio; Guarino Roberto; Padolecchia Gabriella; Leo Carlo; Vigotti Maria Angela; Andreassi Maria Grazia; Latini Giuseppe (BMC, 2012)
Abstract Background Congenital anomalies and their primary prevention are a crucial public health issue. This work aimed to estimate the prevalence of congenital anomalies in Brindisi, a city in southeastern Italy at high risk of environmental crisis. Methods This research concerned newborns up to 28 days of age, born between 2001 and 2010 to mothers resident in Brindisi and discharged with a diagnosis of congenital anomaly. We classified cases according to the coding system adopted by the European Network for the Surveillance of Congenital Anomalies (EUROCAT). Prevalence rates of congenital anomalies in Brindisi were compared with those reported by EUROCAT. Logistic regression models were adapted to evaluate the association between congenital anomalies and municipality of residence of the mother during pregnancy. Results Out of 8,503 newborns we recorded 194 subjects with congenital anomalies (228.2/10,000 total births), 1.2 times higher than the one reported by the EUROCAT pool of registries. We observed 83 subjects with congenital heart diseases with an excess of 49.1%. Odds Ratios for congenital heart diseases significantly increased for newborns to mothers resident in Brindisi (OR 1.75 CI 95% 1.30-2.35). Conclusions Our findings indicated an increased prevalence of Congenital Anomalies (especially congenital heart diseases) in the city of Brindisi. More research is needed in order to analyze the role of factors potentially involved in the causation of congenital anomalies.